The influence of polymer architecture on nanosized hydroxyapatite precipitation - Dogan, Ozlem; Oner, Mualla (AMER SCIENTIFIC PUBLISHERS, 2008)
In this work we present a facile way to produce hydroxyapatite (HAP) nanoparticles by wet chemical synthesis in the presence of polyelectrolytes under controlled temperature, pH, and atmospheric conditions. The resulting calcium rich carbonated HAP is sintered in an air atmosphere to investigate the thermal stability of the synthesized powders. The morphology and microstructure of the HAP nanoparticles were investigated by XRD, SEM, FTIR spectroscopy, thermal analysis, and particle size analyzer. Polyelectrolytes affect the coherent length of the crystalline domain, the dimension and particle size distribution of the crystals. The reduction in size is greater in the direction of the c-axis. The SEM micrograph shows the formation of well-crystallized, agglomerated small particles of HAP The mean size of the subunit is smaller than that of the surface of the grain observed in SEM. X-ray analysis have shown that the resulting particles have high thermal stability.
Keywords: hydroxyapatite; nanoparticles; biornaterials; chemical synthesis; CARBONATED HYDROXYAPATITE; MECHANOCHEMICAL SYNTHESIS; HYDROTHERMAL SYNTHESIS; THERMAL-STABILITY; CRYSTALLIZATION; KINETICS; BONE; POLYELECTROLYTES; AGGREGATION; COMPOSITES; Chemistry; Science & Technology - Other Topics; Materials Science; Physics